Penerapan Rendam Kaki dan Pernapasan Diafragma (Napas Dalam) serta Aromaterapi Lavender untuk Mengurangi Kecemasan pada Ibu Hamil Trimester III di PMB Sugiyastuti, Amd. Keb. - Khotimah, Asih Husnul; Sulastri, Eti (Prosiding University Research Colloquium, 2019)
Anxiety is an emotional reaction that can occur in pregnant women are associated with anxiety. In Indonesia, there are 107 million (28.7%) third- trimester pregnant women who experience anxiety at the time before birth or in the face of labor. Anxiety if not addressed it will have an impact on ongoing emotional changes and can even lead to mental disorders. Efforts to reduce anxiety can use the foot soak, diaphragmatic breathing and aromatherapy lavender. Knowing Giving a foot soak and diaphragmatic breathing (deep breath) as well as aromatherapy lavender to reduce anxiety in the third- trimester pregnant women. Methods of the application used in the application is done using an analytic descriptive method using a case study approach. Taking respondents were 5 people who have a category of pregnant women with anxiety primigravidae third-trimester. The research instrument used to assess the scale HARS anxiety. The data were obtained through interviews, observation, documentation, and literature. The implementation process for 2 weeks, it is evident that there are changes in anxiety scores after application on primigravida pregnant women who experience anxiety third-trimester average respondent suffered mild anxiety and being reduced to no anxiety in the first and second week. Conclusion: The use of innovative foot soak and diaphragmatic breathing and aromatherapy lavender.provaid able to reduce the score of anxiety in pregnant women primigravidae the third-trimester.